Non-responders to treatment with antagonists of vascular endothelial growth factor in age-related macular degeneration. Issue 11 (21st August 2013) - Krebs, Ilse; Glittenberg, Carl; Ansari-Shahrezaei, Siamak; Hagen, Stefan; Steiner, Irene; Binder, Susanne
Abstract : Purpose: Most of the publications on modern therapy of neovascular age-related macular degeneration focus on the effect of the treatment. The purpose of this study is to determine the frequency of non-responders to anti-vascular endothelial growth factor (anti-VEGF) treatment and find possible reasons for their failure to respond. Methods: The records of patients treated until the end of 2008 the first time with either bevacizumab or ranibizumab were reviewed. Based on the availability of measurable results and according to prior publications showing the effect of the therapy, loss of three lines of distance acuity, increase of retinal thickness or lesion size were identified as indicators of non-responders. Two of these three signs had to be present. Results: 334 eyes of 283 patients were included; 74.55% received bevacizumab and 25.45% received ranibizumab. Overall 14.37% of the eyes were identified as non-responders (14.06% in the bevacizumab group and 15.29% in the ranibizumab group). Baseline distance acuity and vitreo-retinal adhesions were significantly correlated with non-responders. Correlations with age, gender, lesion type, other morphologic features, and the kind of anti-VEGF agent failed to be significant. 10.4% of the non-responders showed a delayed but good response to anti-VEGF treatment. Conclusions: About 15% did not sufficiently respond to anti-VEGF treatment. Vitreo-retinal adherences were the only ophthalmologic factor which could be identified to be significantly correlated with insufficient response.